1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
|
------------------------------------------------------------------------------
-- --
-- GNAT RUN-TIME COMPONENTS --
-- --
-- S Y S T E M . E X P _ M O D --
-- --
-- B o d y --
-- --
-- Copyright (C) 1992-2023, Free Software Foundation, Inc. --
-- --
-- GNAT is free software; you can redistribute it and/or modify it under --
-- terms of the GNU General Public License as published by the Free Soft- --
-- ware Foundation; either version 3, or (at your option) any later ver- --
-- sion. GNAT is distributed in the hope that it will be useful, but WITH- --
-- OUT ANY WARRANTY; without even the implied warranty of MERCHANTABILITY --
-- or FITNESS FOR A PARTICULAR PURPOSE. --
-- --
-- As a special exception under Section 7 of GPL version 3, you are granted --
-- additional permissions described in the GCC Runtime Library Exception, --
-- version 3.1, as published by the Free Software Foundation. --
-- --
-- You should have received a copy of the GNU General Public License and --
-- a copy of the GCC Runtime Library Exception along with this program; --
-- see the files COPYING3 and COPYING.RUNTIME respectively. If not, see --
-- <http://www.gnu.org/licenses/>. --
-- --
-- GNAT was originally developed by the GNAT team at New York University. --
-- Extensive contributions were provided by Ada Core Technologies Inc. --
-- --
------------------------------------------------------------------------------
-- Preconditions, postconditions, ghost code, loop invariants and assertions
-- in this unit are meant for analysis only, not for run-time checking, as it
-- would be too costly otherwise. This is enforced by setting the assertion
-- policy to Ignore.
pragma Assertion_Policy (Pre => Ignore,
Post => Ignore,
Ghost => Ignore,
Loop_Invariant => Ignore,
Assert => Ignore);
with Ada.Numerics.Big_Numbers.Big_Integers_Ghost;
use Ada.Numerics.Big_Numbers.Big_Integers_Ghost;
package body System.Exp_Mod
with SPARK_Mode
is
use System.Unsigned_Types;
-- Local lemmas
procedure Lemma_Add_Mod (X, Y : Big_Natural; B : Big_Positive)
with
Ghost,
Post => (X + Y) mod B = ((X mod B) + (Y mod B)) mod B;
procedure Lemma_Exp_Expand (A : Big_Integer; Exp : Natural)
with
Ghost,
Post =>
(if Exp rem 2 = 0 then
A ** Exp = A ** (Exp / 2) * A ** (Exp / 2)
else
A ** Exp = A ** (Exp / 2) * A ** (Exp / 2) * A);
procedure Lemma_Exp_Mod (A : Big_Natural; Exp : Natural; B : Big_Positive)
with
Ghost,
Subprogram_Variant => (Decreases => Exp),
Post => ((A mod B) ** Exp) mod B = (A ** Exp) mod B;
procedure Lemma_Mod_Ident (A : Big_Natural; B : Big_Positive)
with
Ghost,
Pre => A < B,
Post => A mod B = A;
procedure Lemma_Mod_Mod (A : Big_Integer; B : Big_Positive)
with
Ghost,
Post => A mod B mod B = A mod B;
procedure Lemma_Mult_Div (X : Big_Natural; Y : Big_Positive)
with
Ghost,
Post => X * Y / Y = X;
procedure Lemma_Mult_Mod (X, Y : Big_Natural; B : Big_Positive)
with
Ghost,
-- The following subprogram variant can be added as soon as supported
-- Subprogram_Variant => (Decreases => Y),
Post => (X * Y) mod B = ((X mod B) * (Y mod B)) mod B;
-----------------------------
-- Local lemma null bodies --
-----------------------------
procedure Lemma_Mod_Ident (A : Big_Natural; B : Big_Positive) is null;
procedure Lemma_Mod_Mod (A : Big_Integer; B : Big_Positive) is null;
procedure Lemma_Mult_Div (X : Big_Natural; Y : Big_Positive) is null;
-------------------
-- Lemma_Add_Mod --
-------------------
procedure Lemma_Add_Mod (X, Y : Big_Natural; B : Big_Positive) is
procedure Lemma_Euclidean_Mod (Q, F, R : Big_Natural) with
Pre => F /= 0,
Post => (Q * F + R) mod F = R mod F,
Subprogram_Variant => (Decreases => Q);
-------------------------
-- Lemma_Euclidean_Mod --
-------------------------
procedure Lemma_Euclidean_Mod (Q, F, R : Big_Natural) is
begin
if Q > 0 then
Lemma_Euclidean_Mod (Q - 1, F, R);
end if;
end Lemma_Euclidean_Mod;
-- Local variables
Left : constant Big_Natural := (X + Y) mod B;
Right : constant Big_Natural := ((X mod B) + (Y mod B)) mod B;
XQuot : constant Big_Natural := X / B;
YQuot : constant Big_Natural := Y / B;
AQuot : constant Big_Natural := (X mod B + Y mod B) / B;
begin
if Y /= 0 and B > 1 then
pragma Assert (X = XQuot * B + X mod B);
pragma Assert (Y = YQuot * B + Y mod B);
pragma Assert
(Left = ((XQuot + YQuot) * B + X mod B + Y mod B) mod B);
pragma Assert (X mod B + Y mod B = AQuot * B + Right);
pragma Assert (Left = ((XQuot + YQuot + AQuot) * B + Right) mod B);
Lemma_Euclidean_Mod (XQuot + YQuot + AQuot, B, Right);
pragma Assert (Left = (Right mod B));
pragma Assert (Left = Right);
end if;
end Lemma_Add_Mod;
----------------------
-- Lemma_Exp_Expand --
----------------------
procedure Lemma_Exp_Expand (A : Big_Integer; Exp : Natural) is
begin
if Exp rem 2 = 0 then
pragma Assert (Exp = Exp / 2 + Exp / 2);
else
pragma Assert (Exp = Exp / 2 + Exp / 2 + 1);
pragma Assert (A ** Exp = A ** (Exp / 2) * A ** (Exp / 2 + 1));
pragma Assert (A ** (Exp / 2 + 1) = A ** (Exp / 2) * A);
pragma Assert (A ** Exp = A ** (Exp / 2) * A ** (Exp / 2) * A);
end if;
end Lemma_Exp_Expand;
-------------------
-- Lemma_Exp_Mod --
-------------------
procedure Lemma_Exp_Mod (A : Big_Natural; Exp : Natural; B : Big_Positive)
is
begin
if Exp /= 0 then
declare
Left : constant Big_Integer := ((A mod B) ** Exp) mod B;
Right : constant Big_Integer := (A ** Exp) mod B;
begin
Lemma_Mult_Mod (A mod B, (A mod B) ** (Exp - 1), B);
Lemma_Mod_Mod (A, B);
Lemma_Exp_Mod (A, Exp - 1, B);
Lemma_Mult_Mod (A, A ** (Exp - 1), B);
pragma Assert
((A mod B) * (A mod B) ** (Exp - 1) = (A mod B) ** Exp);
pragma Assert (A * A ** (Exp - 1) = A ** Exp);
pragma Assert (Left = Right);
end;
end if;
end Lemma_Exp_Mod;
--------------------
-- Lemma_Mult_Mod --
--------------------
procedure Lemma_Mult_Mod (X, Y : Big_Natural; B : Big_Positive) is
Left : constant Big_Natural := (X * Y) mod B;
Right : constant Big_Natural := ((X mod B) * (Y mod B)) mod B;
begin
if Y /= 0 and B > 1 then
Lemma_Add_Mod (X * (Y - 1), X, B);
Lemma_Mult_Mod (X, Y - 1, B);
Lemma_Mod_Mod (X, B);
Lemma_Add_Mod ((X mod B) * ((Y - 1) mod B), X mod B, B);
Lemma_Add_Mod (Y - 1, 1, B);
pragma Assert (((Y - 1) mod B + 1) mod B = Y mod B);
if (Y - 1) mod B + 1 < B then
Lemma_Mod_Ident ((Y - 1) mod B + 1, B);
Lemma_Mod_Mod ((X mod B) * (Y mod B), B);
pragma Assert (Left = Right);
else
pragma Assert (Y mod B = 0);
pragma Assert (Y / B * B = Y);
pragma Assert ((X * Y) mod B = (X * Y) - (X * Y) / B * B);
pragma Assert
((X * Y) mod B = (X * Y) - (X * (Y / B) * B) / B * B);
Lemma_Mult_Div (X * (Y / B), B);
pragma Assert (Left = 0);
pragma Assert (Left = Right);
end if;
end if;
end Lemma_Mult_Mod;
-----------------
-- Exp_Modular --
-----------------
function Exp_Modular
(Left : Unsigned;
Modulus : Unsigned;
Right : Natural) return Unsigned
is
Result : Unsigned := 1;
Factor : Unsigned := Left;
Exp : Natural := Right;
function Mult (X, Y : Unsigned) return Unsigned is
(Unsigned (Long_Long_Unsigned (X) * Long_Long_Unsigned (Y)
mod Long_Long_Unsigned (Modulus)))
with
Pre => Modulus /= 0;
-- Modular multiplication. Note that we can't take advantage of the
-- compiler's circuit, because the modulus is not known statically.
-- Local ghost variables, functions and lemmas
M : constant Big_Positive := Big (Modulus) with Ghost;
function Equal_Modulo (X, Y : Big_Integer) return Boolean is
(X mod M = Y mod M)
with
Ghost,
Pre => Modulus /= 0;
procedure Lemma_Mult (X, Y : Unsigned)
with
Ghost,
Post => Big (Mult (X, Y)) = (Big (X) * Big (Y)) mod M
and then Big (Mult (X, Y)) < M;
procedure Lemma_Mult (X, Y : Unsigned) is null;
Rest : Big_Integer with Ghost;
-- Ghost variable to hold Factor**Exp between Exp and Factor updates
begin
pragma Assert (Modulus /= 1);
-- We use the standard logarithmic approach, Exp gets shifted right
-- testing successive low order bits and Factor is the value of the
-- base raised to the next power of 2.
-- Note: it is not worth special casing the cases of base values -1,0,+1
-- since the expander does this when the base is a literal, and other
-- cases will be extremely rare.
if Exp /= 0 then
loop
pragma Loop_Invariant (Exp > 0);
pragma Loop_Invariant (Result < Modulus);
pragma Loop_Invariant (Equal_Modulo
(Big (Result) * Big (Factor) ** Exp, Big (Left) ** Right));
pragma Loop_Variant (Decreases => Exp);
if Exp rem 2 /= 0 then
pragma Assert
(Big (Factor) ** Exp
= Big (Factor) * Big (Factor) ** (Exp - 1));
pragma Assert (Equal_Modulo
((Big (Result) * Big (Factor)) * Big (Factor) ** (Exp - 1),
Big (Left) ** Right));
pragma Assert (Big (Factor) >= 0);
Lemma_Mult_Mod (Big (Result) * Big (Factor),
Big (Factor) ** (Exp - 1),
Big (Modulus));
Lemma_Mult (Result, Factor);
Result := Mult (Result, Factor);
Lemma_Mod_Ident (Big (Result), Big (Modulus));
Lemma_Mod_Mod (Big (Factor) ** (Exp - 1), Big (Modulus));
Lemma_Mult_Mod (Big (Result),
Big (Factor) ** (Exp - 1),
Big (Modulus));
pragma Assert (Equal_Modulo
(Big (Result) * Big (Factor) ** (Exp - 1),
Big (Left) ** Right));
Lemma_Exp_Expand (Big (Factor), Exp - 1);
pragma Assert (Exp / 2 = (Exp - 1) / 2);
end if;
Lemma_Exp_Expand (Big (Factor), Exp);
Exp := Exp / 2;
exit when Exp = 0;
Rest := Big (Factor) ** Exp;
pragma Assert (Equal_Modulo
(Big (Result) * (Rest * Rest), Big (Left) ** Right));
Lemma_Exp_Mod (Big (Factor) * Big (Factor), Exp, Big (Modulus));
pragma Assert
((Big (Factor) * Big (Factor)) ** Exp = Rest * Rest);
pragma Assert (Equal_Modulo
((Big (Factor) * Big (Factor)) ** Exp,
Rest * Rest));
Lemma_Mult (Factor, Factor);
Factor := Mult (Factor, Factor);
Lemma_Mod_Mod (Rest * Rest, Big (Modulus));
Lemma_Mod_Ident (Big (Result), Big (Modulus));
Lemma_Mult_Mod (Big (Result), Rest * Rest, Big (Modulus));
pragma Assert (Big (Factor) >= 0);
Lemma_Mult_Mod (Big (Result), Big (Factor) ** Exp,
Big (Modulus));
pragma Assert (Equal_Modulo
(Big (Result) * Big (Factor) ** Exp, Big (Left) ** Right));
end loop;
pragma Assert (Big (Result) = Big (Left) ** Right mod Big (Modulus));
end if;
return Result;
end Exp_Modular;
end System.Exp_Mod;
|